Contaminants analyzed from multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound, 2007-2008 - Fisk, Aaron; McKinney, Melissa; Muir, Derek; Tomy, Gregg (Canadian Cryospheric Information Network, 2012)
Samples of mixed zooplankton (mainly Calanus spp.), two benthic invertebrate (scallop Chlamys islandica, snail Buccinum cyaneum), five teleost fish (herring Clupea harengus, capelin Mallotus villosus, char Salvelinus alpines, sculpin Myoxocephalus scorpioides, turbot Reinhardtius hippoglossoides), two elasmobranch fish (arctic skate Amblyraja hyperborea, Greenland shark Somniosus microcephalus), two pinniped (harp seal Pagophilus groenlandicus, ringed seal Pusa hispida) and two cetacean (beluga whale Delphinapterus leucas , narwhal Monodon monoceros) species were collected from Cumberland Sound (Nunavut). Zooplankton were sampled by surface horizontal tows and vertical hauls using a plankton net. Benthic invertebrates were sampled by ponar, herring, char and sculpin by gillnet, capelin by dip net and turbot, arctic skate and Greenland sharks by bottom long line. Marine mammals were sampled during Inuit subsistence hunts. Polychlorinated biphenyl (PCB), chlorobenzene (ClBz), hexachlorocyclohexane (HCH), chlordane-related (CHL) and dichlorodiphenyltrichloroethane-related (DDT) contaminants were extracted from whole zooplankton, soft tissues of scallop and snail, muscle tissues of fish and blubber tissue of marine mammals by established methods. Contaminants were extracted from homogenized tissues into organic solvents. A small aliquot was analyzed for gravimetrically for lipid content. Remaining extracts were cleaned up, fractionated and analyzed by gas chromatograph equipped with an electron capture detector. Accuracy of generated contaminant concentrations was usually within 20% of accepted values, assessed by simultaneous extraction and analysis of NIST mussel standard reference material 1974b. Samples extracted in duplicate showed precision in sum (∑) contaminant concentrations on average within 10%, 14%, 19%, 13% and 20% for ∑PCB, ∑ClBz, ∑HCH, ∑CHL and ∑DDT, respectively. Contaminant concentrations in blanks were generally low (<0.05 ng/g). Average method detection limits were 0.02 ng/g. Reported analyte concentrations were blank-subtracted, but not recovery corrected. Stable isotopes of nitrogen and carbon were also assessed in these same samples, except muscle tissues for marine mammals, to investigate the relationship of contaminant concentrations to trophic positions and carbon sources. : Purpose: As the largest fish and most prolific eater in the Arctic seas, the Greenland shark is a very unique vertebrate in the Arctic ecosystem. Given their diet, Greenland sharks hold a position in the food web similar to that of polar bears. Little is known about how these sharks behave or how their behaviour might shift in response to changes in climate. Given their importance in the Arctic food web, this project is assessing the feeding ecology and behaviour of the Greenland shark under different ice conditions to determine how different environments affect this fish. This assessment involves the analysis of contaminants that were found in multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound in 2007 and 2008. : Summary: Not Applicable